2018
DOI: 10.1016/j.appet.2017.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Emotion-driven impulsiveness and snack food consumption of European adolescents: Results from the I.Family study

Abstract: We aimed to investigate the association between emotion-driven impulsiveness and snack food consumption in 1039 European adolescents aged 12-18 years. During the cross-sectional examination in 2013/2014, complete information was collected on: emotion-driven impulsiveness (using the negative urgency subscale from the Urgency, Premeditation, Perseverance, Sensation seeking, and Positive urgency (UPPS-P) Impulsive Behaviour Scale) and snacking behaviour operationalised as 1) consumption frequency of daily snacks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 64 publications
0
18
0
1
Order By: Relevance
“…Furthermore, negative urgency was shown to predict binge eating symptoms prospectively from elementary school to middle school and in college students (Pearson et al, 2015) and adults (Farstad et al, 2015). Negative urgency was also associated with more frequent snacking in adolescents (Smith and Cyders, 2016; Coumans et al, 2018). A path analysis study of 315 patients with eating disorders on the binge spectrum found that low self-directedness and emotional regulation were broadly associated with eating psychopathology, whereas negative urgency was uniquely associated with food addiction (Wolz et al, 2017).…”
Section: Negative Urgency and Addiction: Tobacco Alcohol Cocaine Pmentioning
confidence: 99%
“…Furthermore, negative urgency was shown to predict binge eating symptoms prospectively from elementary school to middle school and in college students (Pearson et al, 2015) and adults (Farstad et al, 2015). Negative urgency was also associated with more frequent snacking in adolescents (Smith and Cyders, 2016; Coumans et al, 2018). A path analysis study of 315 patients with eating disorders on the binge spectrum found that low self-directedness and emotional regulation were broadly associated with eating psychopathology, whereas negative urgency was uniquely associated with food addiction (Wolz et al, 2017).…”
Section: Negative Urgency and Addiction: Tobacco Alcohol Cocaine Pmentioning
confidence: 99%
“…This finding is supported by Rangan et al [47], but not by two other studies in which girls with poor sleep quality tended to consume carbohydrate-rich foods [47, 48]. It seems that negative emotion may be responsible for the selection of sweet and high fat foods with more palatability [49, 50]. The present study could not confirm emotional eating as a mediator between poor sleep quality and more energy intake from fat, which is in contrast with Dweck et al’s study that reported short sleep duration resulted in more food intake in subjects who were emotional eaters [23].…”
Section: Discussionmentioning
confidence: 91%
“…Many foods included in the unhealthy diet pattern (i.e., fast foods, ice cream, fried food, French fries, potato chips, cakes, and sugar-sweetened sodas) are ready to eat and are easily obtainable, even for 9–11-year-olds. However, one cause of EE may be poor emotion regulation in general [4], and it has been shown that adolescents (mean age 13.6 years) who are having difficulties with adequately regulating their negative emotions consume snacks, especially energy-dense snacks, more frequently [48]. Yet, because our study, as well as most of the earlier research regarding the association between emotional eating and diet, was cross-sectional, we cannot rule out the possibility of a reverse relationship.…”
Section: Discussionmentioning
confidence: 99%